Preparation of highly efficient NiB catalyst via triton-stabilized for alkaline NaBH4 hydrolysis reaction - Elcicek, Huseyin; Erol, Mahmut; Ozdemir, Oguz Kaan (WILEY, 2021)
The development of highly active and cost effective catalysts for hydrolysis of sodium borohydride (NaBH4) is the main aim for practical usage of NaBH4 for fuel cells. Herein, we investigated the addition of various amounts of Triton during chemical reduction process on the NiB catalytic activity. The experimental results indicated that the catalytic performance of Triton stabilized NiB catalysts was significantly higher than that of NiB catalysts. Furthermore, the highest hydrogen generation rate in NaBH4 hydrolysis was obtained with 25 mu L Triton addition as 8970 mL.min(-1).g(cat)(-1) at 338 K. The activation energy of the hydrolysis for NiB25 and NiB catalysts were calculated as 48.05 and 58.91 kJ mol(-1), respectively. In the second part of this study, the kinetic performance of NaBH4 hydrolysis was experimentally studied, and subsequently generated hydrogen from the hydrolysis reaction was fed directly to the fuel cell and the performance analysis were investigated. It was found that the power density of pure hydrogen was lower than the hydrogen generated by the NiB25 catalysts. Our results clearly indicated that Triton possessed a significant effect on the catalytic activity of NiB catalyst.
Keywords: NaBH4 hydrolysis; NiB; PEM; surfactant; triton X-100; SODIUM-BOROHYDRIDE SOLUTION; HYDROGEN GENERATION; CO-B; NICKEL(0) NANOCLUSTERS; AMMONIA BORANE; NANOPARTICLE; OPTIMIZATION; SURFACTANTS; PLATINUM; WATER; Energy & Fuels; Nuclear Science & Technology